THE PROCESS OF ORGANIZATION OF THE TASHKENT MEDICAL ACADEMY (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article provides a historical analysis of the establishment process of the Tashkent Medical Academy. The academy's contribution to the development of Uzbekistan's medical sector and its influence on the organization of modern medical education are also analyzed.